Successful alternative treatment of extensively drug-resistant tuberculosis in Argentina with a combination of linezolid, moxifloxacin and thioridazine - Abbate, Eduardo (2012)
Fil: Abbate, Eduardo. Instituto de Tisioneumonología ‘Prof. Dr. Raúl Vaccarezza’, Universidad de Buenos Aires; Argentina.